Schaum's Solved Problems Series 800 Solved Problems in Vector Mechanics For Engineers: Statics - SHELLY, Joseph F. (McGraw Hill, 1990)
Schaum's Solved Problems Series 800 Solved Problems in Vector Mechanics For Engineers: Statics